Short-term changes in opinions on refugees from Ukraine - Galgóczi, Eszter; Petrovics, Nándor (POLARITIES, 2024)
Since the outbreak of the migration crisis in 2015, the perception of migrants and refugees has been a dominant topic in public discourse in Hungary. In numerous cases, political actors have focused their narratives on the arrivals, which has provoked considerable public resentment. In February 2022, with the outbreak of the Russian-Ukrainian war, a new situation arose, with hundreds of thousands of people arriving in the country from Ukraine at the same time Our study examines whether, in the relatively short term, public opinion towards refugees might change when arrivals come from a neighbouring country with a more or less similar culture.